DETERMINATION OF GENETIC MUTATIONS INDUCED BY CHEMICAL AND RADIATION TREATMENT IN AEGLE MARMELOS, USING INTER SIMPLE SEQUENCE REPEAT (ISSR) PRIMERS. - SHUBHADA WALVEKAR,; DR. PRASANNA KAIMAL, (International Journal of Pharma and Bio Sciences, 2014)
Induced mutations in in vitro grown shoots of Aegle marmelos Corr. ( Bael) due to the treatment with colchicines, Diethyl sulphate and gamma radiations were screened using fifteen ISSR and five RAPD primers were used for the testing of variability and reproducibility of the band. High level of genetic variation among the control and plantlets treated with three different mutagens was observed. Thirteen Out of 15 ISSR primers used for initial screening showed polymorphic profile which together produced 83 bands across four mutagenic variants of A. marmelos, of which 59 bands were polymorphic showing 71% polymorphism. The plants treated with colchicine grouped closer to control plant indicating lesser variation, DES treated plants in spite of major loss of genetic material showed better resemblance to control plants than gamma rays which has maximum level of mutations, grouping far away from the control plants